2017
DOI: 10.1101/mcs.a001743
|View full text |Cite
|
Sign up to set email alerts
|

Novel de novo variant in EBF3 is likely to impact DNA binding in a patient with a neurodevelopmental disorder and expanded phenotypes: patient report, in silico functional assessment, and review of published cases

Abstract: Pathogenic variants in EBF3 were recently described in three back-to-back publications in association with a novel neurodevelopmental disorder characterized by intellectual disability, speech delay, ataxia, and facial dysmorphisms. In this report, we describe an additional patient carrying a de novo missense variant in EBF3 (c.487C>T, p.(Arg163Trp)) that falls within a conserved residue in the zinc knuckle motif of the DNA binding domain. Without a solved structure of the DNA binding domain, we generated a hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…The splice site variant, c.486-1G>A, may also cause the loss of the splice acceptor site and induce skipping of exon 6, which encodes the conserved zinc knuckle motif in the COE1 DBD. Molecular modeling of EBF3 mutations at the zinc knuckle has demonstrated decreased DNA affinity resulting in aberrant DNA binding ( Blackburn et al 2017 ). Altered expression or binding of EBF3 is likely responsible for the predominance of neurological symptoms seen in our patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The splice site variant, c.486-1G>A, may also cause the loss of the splice acceptor site and induce skipping of exon 6, which encodes the conserved zinc knuckle motif in the COE1 DBD. Molecular modeling of EBF3 mutations at the zinc knuckle has demonstrated decreased DNA affinity resulting in aberrant DNA binding ( Blackburn et al 2017 ). Altered expression or binding of EBF3 is likely responsible for the predominance of neurological symptoms seen in our patients.…”
Section: Discussionmentioning
confidence: 99%
“…EBF3 is within a shared deletion of Chromosome 10q26.3 in many of these patients. Four recent reports identified a total of 20 unrelated individuals and two siblings who have de novo variants in EBF3 and a distinct neurodevelopmental syndrome ( Blackburn et al 2017 ; Chao et al 2017 ; Harms et al 2017 ; Sleven et al 2017 ). Here we add further evidence for the role of EBF3 in brain development and expand the phenotype of this syndrome caused by pathogenic variants in EBF3 .…”
Section: Introductionmentioning
confidence: 99%
“…We found, in mice, that mEbf1 and mEbf2 are implicated in axial MN development. In the embryonic mouse spinal cord, mEbf1 is selectively expressed in hypaxial muscle-innervating MNs (HMC), while mEbf2 is expressed in epaxial muscle-innervating MNs [17,[42][43][44][45][46], our findings could help advance our understanding of these conditions.…”
mentioning
confidence: 80%
“…Greater function and mechanistic resolution are required in order to properly treat patients with these variants. Previous studies by our lab [ 33 , 34 ] and others [ 35 , 36 ] have demonstrated that computational studies can generate novel data to strongly support the interpretation of variants identified from high-throughput sequencing and also to generate detailed mechanistic hypotheses for their underlying atomic mechanisms. When paired with detailed computational analysis, candidate mechanisms can be proposed at the atomic level to unify experimental observations with prior knowledge from the literature into a coherent mechanism of molecular dysfunction, driven by genetic variants.…”
Section: Discussionmentioning
confidence: 99%